Discovery and characterization of small molecule inhibitors of cystathionine gamma‐synthase with in planta activity. Issue 9 (12th May 2021) - Bloch, Itai; Haviv, Hadar; Rapoport, Irena; Cohen, Elad; Shushan, Rotem Shelly Ben; Dotan, Nesly; Sher, Inbal; Hacham, Yael; Amir, Rachel; Gal, Maayan
Summary: The synthesis of essential amino acids in plants is pivotal for their viability and growth, and these cellular pathways are therefore targeted for the discovery of new molecules for weed control. Herein, we describe the discovery and design of small molecule inhibitors of cystathionine gamma‐synthase, a key enzyme in the biosynthesis of methionine. Based on in silico screening and filtering of a large molecular database followed by the in vitro selection of molecules, we identified small molecules capable of binding the target enzyme. Molecular modelling of the interaction and direct biophysical binding enabled us to explore a focussed chemical expansion set of molecules characterized by an active phenyl‐benzamide chemical group. These molecules are bio‐active and efficiently inhibit the viability of BY‐2 tobacco cells and seedlings growth of Arabidopsis thaliana on agar plates.